2020
DOI: 10.1177/0011128720974309
|View full text |Cite
|
Sign up to set email alerts
|

Citizens’ Perceptions of Over- and Under-Policing: A Look at Race, Ethnicity, and Community Characteristics

Abstract: While there is substantial research on community-police relations, most studies examine the abstract outcome of “negative perceptions of police.” This study, however, examines over- and under-policing as two distinct, yet not mutually exclusive, constructs, suggesting that there is more to strained police-community relations than citizens perceiving the police “negatively.” Using the Project on Human Development in Chicago Neighborhoods Community Survey, we assess the relationship between race and ethnicity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 84 publications
(110 reference statements)
0
22
1
Order By: Relevance
“… 7 In this study, we define overpolicing as the disproportionate targeting of Black communities by law enforcement that does not correlate to the incidence of crime within neighborhoods but rather reflects racist beliefs about Black deviance. 9 , 10 Research has shown that men report increased psychological distress in neighborhood-level increases in aggressive policing (ie, frisking and use of force by police). 11 However, to our knowledge, there is no literature that seeks to understand how aggressive policing and increased police surveillance affect maternal and infant health, specifically PTB.…”
Section: Introductionmentioning
confidence: 99%
“… 7 In this study, we define overpolicing as the disproportionate targeting of Black communities by law enforcement that does not correlate to the incidence of crime within neighborhoods but rather reflects racist beliefs about Black deviance. 9 , 10 Research has shown that men report increased psychological distress in neighborhood-level increases in aggressive policing (ie, frisking and use of force by police). 11 However, to our knowledge, there is no literature that seeks to understand how aggressive policing and increased police surveillance affect maternal and infant health, specifically PTB.…”
Section: Introductionmentioning
confidence: 99%
“…Further, studies have shown that communities that experience police violence may later struggle with negative outcomes (e.g., PTSD, substance abuse); therefore, disseminating public health resources to these communities in the aftermath of such incidents may ameliorate the negative consequences of such trauma [4,33]. In the aftermath of police violence, the historically strained relationship between police and communities of color [34] will worsen and potentially negatively affect police-community relationships, which may contribute to greater under-reporting of crime by residents of minority communities. Reducing police violence would likely help mitigate this tense relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent police contact can also deteriorate trust in institutions and exacerbate “system avoidance,” with individuals less willing to seek out government services, contributing to social stratification ( 30 ). In addition to these potential harms of over-policing traffic violations, under-policing can also create equity issues by heightening risks for both drivers and pedestrians in neighborhoods with lax enforcement ( 31 ).…”
Section: Discussionmentioning
confidence: 99%